Topography of glycosylation in yeast: characterization of GDPmannose transport and lumenal guanosine diphosphatase activities in Golgi-like vesicles. - Abeijon, C (1989)
"Outer-chain" addition of mannose residues to yeast glycoproteins occurs in the Golgi compartment of the cell. Essential steps in this process are thought to include transport of GDPmannose from the cytoplasm into the lumen of Golgi vesicles, transfer of mannose to glycoprotein acceptors, hydrolysis of the resulting GDP to GMP, and return of GMP and inorganic phosphate to the cytoplasm. We report detection and characterization of a GDPmannose transport activity and a GDPase by yeast vesicles. The active transport of GDPmannose as well as the GDPase and another presumed Golgi enzyme, alpha 1,2-mannosyltransferase, are concentrated in a subcellular fraction that can be partially separated, by velocity sucrose gradient centrifugation, from a fraction enriched in an endoplasmic reticulum marker enzyme.